Solvent-Free Synthesized Zeolites NaA-Supported Binary Nickel-Silver Nanoparticles and Their Use as an Efficient Catalyst for Hydrodechlorination of 2,4-Dichlorophenol - Thanh Thien Co; Thi Yen Nhi Nguyen; Ngoc Thao Nguyen Du; Thien An Nguyen; Thanh Binh Nguyen; Thi Duyen Diep; Le Thanh Nguyen Huynh; Viet Hai Le (International Journal of Chemical Engineering)
Using a solvent-free method, zeolite NaA was synthesized from raw kaolin, collected from Binh Duong, Vietnam. The synthesis involved thermal hydration under an alkaline solution. The catalysts based on binary nickel-silver nanoparticles were prepared through in situ reduction of metal salts in aqueous zeolitic suspension using sodium borohydride as a reducing agent. The catalysts were fully characterized by various techniques such as X-ray diffraction (XRD), Fourier transform infrared (FT-IR), scanning electron microscopy (SEM), energy-dispersive X-ray (EDX), transmission electron microscopy (TEM), and Brunauer–Emmett–Teller (BET). The physicochemical properties of these catalysts were studied in detail, in which the formation of body-centered cubic crystal zeolite NaA (1-2 μm) containing the spherical shape of metallic nanoparticles with a particle size around 8–20 nm was observed. The hydrodechlorination of 2,4-dichlorophenol was performed to confirm the high catalytic activity and stability of the 10%NiAg/ZA catalyst. The results showed that the catalyst achieved over 91% conversion initially and 73% conversion after five re-uses.